A court of frost and starlight - Maas, Sarah J. (Court of Thorns and Roses, 2018)
"As Feyre navigates her first Winter Solstice as High Lady, she finds that those dearest to her have more wounds than she anticipated--scars that will have far-reaching impact on the future of their Court"--Provided by publisher.